ANALISIS NILAI PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dhia Fairuz Izdihar; Nurjanti Takarini (Journal of Economics Development Issues, 2021)
Firm value occurs because stock prices fluctuate. The stock price states the value of the company, if the company has a good performance, the interest of investors will be high, the share price will increase and the company value will also increase. This research aims to analyze the effect of profitability, investment decisions, and dividend policy on firm value in food and beverages companies on the Indonesia Stock Exchange. The research sample used is a food and beverage company that is listed and active in the capital market, and shares financial data during the 2015-2018 period, as well as companies that distribute dividends during the 2015-2018 period. The total population of this research is 26 food and beverages companies. The sample selection process using purposive sampling method obtained 16 food and beverages companies. This research uses secondary data in the form of financial reports published on the (IDX). The analysis method used is multiple linier regression, classical assumption test, t test and F test. The results of this research indicate that only profitability is capable of increasing firm value, while investment decisions and dividend policy are not able to increase firm value. Keywords : Profitability, Investment Decision, Dividend Policy, and Firm Value.